PENERAPAN MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN BIOLOGI - Rajagukguk, Salome; Perayanti Sinaga, Dian; Irawan Sipayung, Miranda (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This research is about the implementation of the Student Teams Achievement Division (STAD) learning model to improve students' motivation and learning outcomes in Biology. The study was conducted at SMA Al Alwasliyah in Pematangsiantar City, involving XI MIPA class students in the 2024/2025 academic year. This research is a Classroom Action Research (CAR) that uses both qualitative and quantitative methods. It was carried out in two cycles, each consisting of the stages of planning, action, observation, and reflection. The sample consisted of 21 students from class XI MIPA.The research instruments used to collect data included observation sheets, motivation questionnaires (with a minimum completeness criterion of 75% for learning motivation), and achievement tests (with a minimum completeness score of 80 based on the school's minimum mastery criteria/Kriteria Ketuntasan Minimal or KKM). Data analysis was then conducted.The results showed that students' learning motivation improved from an average score of 60.15% in the first cycle to 79.9% in the second cycle. Similarly, students’ learning outcomes increased from 66.66% mastery in the first cycle to 95.23% in the second cycle.Based on the data analysis, it can be concluded that the implementation of the Student Teams Achievement Division (STAD) learning model significantly improves both students’ learning motivation and academic achievement in Biology, particularly on the topic of biodiversity, according to the school's mastery criteria.